Correlation between theory of internal esteem need of Maslow’s Hierarchy and Speaking ability of the students at English Study Program FKIP-UIR Pekanbaru - Erna Nawir (UIR Press, 2016)
Internal Esteem Need is one of the important motivations that affect students’ achievement in learning as their internal motivations. This paper addresses a study of finding out whether any significant correlation between theory of internal esteem of Maslow and the students’ speaking ability at English Study Program FKIP UIR Pekanbaru. The population is all the fifth (5th) year of English students of English Study Program FKIP UIR who have just taken Speaking 2 (Scientific Discussion) in the second semester with 40 students randomly chosen as sample. A questionnaire of 42 statements were constructed from the indicators of internal esteem of Maslow’s theory and the students’ final grade on their chosen subject were taken to find out the students’ internal esteem and their speaking ability. The result of the study showed that there is no significant relationship between the students’ internal esteem toward their speaking ability.